Analysis of Solution-Focused Brief Therapy Theories and Counseling Techniques in Islamic View - Sholihah, Maidatus; Mierrina, Mierrina; Thohir, Mohamad (Institut Agama Islam Daruttaqwa Gresik, 2024)
This article aims to explain and understand the Solution Focused Brief Therapy (SFBT) technique and its development. This article uses the literature review method by discussing themes through relevant books and journals. The analysis technique used is content analysis. The results of this article show that the process of SFBT techniques and approaches need to carry Islamic values so that it does not only treat physically but also forms a kaffah Muslim by Islamic teachings. The reliability of a counselor is also needed so that this rapid counseling technique can run optimally. Islam-based SFBT not only helps counselors deal with life's problems but also helps them achieve worldly and afterlife happiness and peace of mind, by living life by the rules and instructions of Allah SWT. This method encourages counselors to focus on solutions and their potential so that they can overcome problems effectively and build a better future. The combination of the SFBT approach and Islamic values provides a powerful and holistic framework for counseling, helping individuals develop mentally, emotionally, and spiritually.